The new law on foreign interference: What's next for businesses? - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2021)
The Foreign Interference (Countermeasures) Bill (Fica) was passed in Parliament on Monday after about 10 hours of impassioned debate. Despite the government agreeing to several amendments proposed by the Workers' Party, the substance was not changed in any significant way. Although the government provided more details on how Fica is to operate, more details will be unveiled when it comes into operation. What does all this mean for businesses?